A resource management scheme and its performance analysis for integrated wireless and mobile networks with multiple traffic. (2015) - Zhang, Zhen-Jiang; Zeng, Qing-An; Shen, Wei; Chiang, Hua-Pei; Huang, Yueh-Min
Wireless and mobile networks have experienced a great success in the past few years. However, any single type of network cannot provide all types of services. An integrated wireless and mobile network is introduced by combining different types of networks to provide more comprehensive services, but it imposes great challenges such as efficient resource management for supporting multiple services. However the existing resource management schemes mainly focus on multiple traffic in a single type of wireless and mobile network or a single type of traffic in an integrated wireless and mobile network. In this paper, we propose a resource management scheme to support multiple traffic in an integrated wireless and mobile network. An algorithm is also designed to solve the unfairness problem of resource management between the real-time and non-real-time traffic due to the real-time traffic is delay sensitive and the non-real-time traffic can tolerant some delays.